2004
DOI: 10.1210/en.2003-1382
|View full text |Cite
|
Sign up to set email alerts
|

Photoperiodic Regulation of Leptin Sensitivity in the Siberian Hamster, Phodopus sungorus, Is Reflected in Arcuate Nucleus SOCS-3 (Suppressor of Cytokine Signaling) Gene Expression

Abstract: We present the first evidence that suppressor of cytokine signaling-3 (SOCS3), a protein inhibiting Janus kinase/signal transducer and activator of transcription (STAT) signaling distal of the leptin receptor, conveys seasonal changes in leptin sensitivity in the Siberian hamster. Food deprivation (48 h) reduced SOCS3 gene expression in hamsters acclimated to either long (LD) or short (SD) photoperiods, suggesting that leptin signals acute starvation regardless of photoperiod. However, SOCS3 mRNA levels were s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

22
122
1
5

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 96 publications
(150 citation statements)
references
References 17 publications
22
122
1
5
Order By: Relevance
“…The distribution of SOCS3, NPY, AgRP, POMC and CART mRNAs in the field vole hypothalamus was consistent with other rodent species , Peacock et al2004, Tups et al 2004. Although the probe for SOCS3 hybridized to the ARC, ventromedial and dorsomedial nuclei, expression outside the ARC was highly variable and generally not strong enough to allow quantification by image analysis.…”
Section: Neuroendocrine Correlates Of Leptin Sensitivity and Resistancesupporting
confidence: 86%
See 2 more Smart Citations
“…The distribution of SOCS3, NPY, AgRP, POMC and CART mRNAs in the field vole hypothalamus was consistent with other rodent species , Peacock et al2004, Tups et al 2004. Although the probe for SOCS3 hybridized to the ARC, ventromedial and dorsomedial nuclei, expression outside the ARC was highly variable and generally not strong enough to allow quantification by image analysis.…”
Section: Neuroendocrine Correlates Of Leptin Sensitivity and Resistancesupporting
confidence: 86%
“…Specifically, transfer of male Siberian hamsters from LD to SD conditions was associated with rapid down-regulation of hypothalamic SOCS3 mRNA followed by a decrease in body mass (Tups et al 2004), whereas transfer back from SD to LD induced an increase in SOCS3 expression that preceded any changes in body mass by at least 2 weeks (Tups et al 2006). Furthermore, neural cell-specific SOCS3 conditional knockout mice have greater responsiveness to the weight-and appetite-reducing effects of exogenous leptin than their wild-type littermates (Mori et al 2004).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, we recently showed that leptin exhibits a potent acute glucose-lowering capacity in Lep ob/ob mice, which was associated with increasing the number of pAKT immunoreactive cells in the ARC, thereby sensitizing insulin action (26). It is conceivable that diet-induced hypothalamic inflammation leads to relative leptin insensitivity, involving NF-kB-mediated transcription of the most prominent leptin inhibitor, SOCS-3 (34,35), which is a target gene regulated by this transcription factor (14). Inhibition of IKKb/NF-kB signaling in the ARC was associated with a reduction of SOCS-3 expression in this nucleus.…”
Section: Discussionmentioning
confidence: 99%
“…To test whether ARC-directed AAV overexpression of IkBa-mt might alter leptin sensitivity on a molecular level, we investigated the expression of SOCS-3 as the most prominent inhibitor of leptin signaling (34,35). In situ hybridization analysis revealed that SOCS-3 mRNA was decreased by 35% in the ARC of AAV2-IkBa-mt mice relative to controls (P = 0.029) (Fig.…”
Section: Arcuate Gene Expression Of Socs-3 Is Decreased In Response Tmentioning
confidence: 99%